2017
DOI: 10.1093/neuros/nyx084
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival with Decreased Wait Time to Surgery in Glioblastoma Patients Presenting with Seizure

Abstract: Seizure as the only preoperative symptom independently improved survival, however, when patients developed additional preoperative symptoms, typically due to surgical delay, no prognostic benefit was observed. Prompt diagnosis and neurosurgical intervention is warranted in patients with seizures without other preoperative symptoms to preserve their favorable prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
3
24
0
1
Order By: Relevance
“…Younger age and better KPS are well-known important positive prognostic factors for GBMs in literature. 2 5 , 13 ) In the present study only age below 65 years was a significant prognostic factor for longer OS both in uni and multivariate analysis. Pre-operative KPS was associated with better OS only at univariate Cox regression.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Younger age and better KPS are well-known important positive prognostic factors for GBMs in literature. 2 5 , 13 ) In the present study only age below 65 years was a significant prognostic factor for longer OS both in uni and multivariate analysis. Pre-operative KPS was associated with better OS only at univariate Cox regression.…”
Section: Discussionsupporting
confidence: 46%
“…In this scenario, Flanigan et al 5) recently published a retrospective series of 443 patients with pre-operative rate of seizure of 28% in which multivariate analysis revealed pre-operative epilepsy to be independently associated with increased survival. However, the same authors reported that, in case of longer delay between time of epilepsy at clinical onset and surgery, the prognostic benefit of pre-operative seizure does not seem significant.…”
Section: Discussionmentioning
confidence: 99%
“…Although they reduce the patient quality of life, seizures as a symptom are positively correlated to longer survival in glioblastoma patients [60][61][62]. However, in cases where there is a longer delay between epileptic seizures as a symptom and surgical resection of tumor, this correlation does not seem to be significant [62,63].…”
Section: Long-term Glioblastoma Survivorsmentioning
confidence: 99%
“…Several previous reports have addressed the association between SAO occurrence and glioblastoma survival, both with positive 2 , 4–8 and negative 9–17 results. The majority of recent studies has specifically focused on the role of antiepileptic drugs (AED) on the survival effect of SAO.…”
mentioning
confidence: 99%